Fill the Void [videorecording (DVD)] = Lemale et ha'chalal : torn between her heart and her family - Burshtein, Rama, 1967-; Yaron, Hadas, 1990-; Klein, Yiftach, 1972-; Sheleg, Irit (Sony Pictures Home Entertainment, 2013)
A devout 18-year-old Israeli is pressured to marry the husband of her late sister. Declaring her independence is not an option in Tel Aviv's ultra-Orthodox Hasidic community, where religious law, tradition and the rabbi's word are absolute.